Electronic government and social impact in the life of colombian (2015)
The progress we have had the information and communications technology in Colombia in recent years has been significant ; today it is more common to use technology in everyday lives of people and of both public and private companies , with the aim of making things easier and greater access to information; for this reason the government has been present at every stage of development of Information Technology and Communications (ICT ) in the country , generating control tools , innovation, access and approach to citizenship, but really what was the social impact generated by the electronic government in the lives of Colombians